Decision-making styles among norwegian soccer coaches: An analysis of decision-making style in relation to elite and non-elite coaching and level of playing history - Griffiths, M. A.; Armour, K. M. (International Journal of Sports Science and Coaching, 2013)
The purpose of this study was to investigate soccer coaches' decision-making styles in relation to elite and non-elite coaching experience and level of playing history. A basic assumption was that leader efficiency in soccer is heavily dependent on the quality of the coach's decisions. Efficient decisions are related to experience, and it is not unreasonable that involvement in the soccer context is associated with differences in decision-making style. In this study, decision-making style was defined as a learned habitual response pattern exhibited by an individual when confronted with a decision situation. To assess coaches' decision-making style, we used the General Decision-Making Style (GDMS) scale. Ninety-nine male football coaches in Norway with a mean age of 41 and mean coaching experience of 13.26 years volunteered to participate in the study. The results show that soccer coaches tend to be predominantly rational or intuitive in their decision-making style, with almost no evidence of the avoidant decision-making style. Experts in a domain are characterised by greater use of intuition in their decision-making than non-experts. The results support this assumption, showing that coaches with elite coaching experience seem to have a greater preference for intuitive or rational decision-making style than do other coaches. Soccer coaches with elite-level player experience also use intuitive or rational decision-making styles significantly more often than coaches lacking such experience, suggesting a connection between involvement in a community of practice and soccer coaches' decision-making style. Further research should expand our scientific knowledge about how soccer coaches make decisions in different contexts and clarify strategies for facilitating decision-making in coaching.